2013
DOI: 10.7202/1015640ar
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessment of Professional Growth Through Reflective Portfolios

Abstract: This study aims to discern how teacher candidates develop reflective capacity by self-assessing their portfolios. While the goal was to help first-year teacher candidates assess their progress toward achieving provincial teaching competencies, many called attention to the interconnections between their academic artifacts and their personal profiles. This led the researcher to refine the focus of the portfolio to the emergence of professional identity and developing structures to support this type of self-aware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The fourth major benefit that we identified from the survey data involved the peer mentors' ability to ask probing questions that made the first-year students to think more deeply about their field placement experiences (8 comments from 53 surveys). Another member of our MRU Education Department has previously observed that first-year students in our teacher education program often take a surface approach when they are journaling about their field placement experiences (Nickel, 2013). They simply describe the setting of a classroom rather than questioning and probing the learning and teaching transactions taking place within this environment.…”
Section: Probing Questions To Think Deepermentioning
confidence: 99%
“…The fourth major benefit that we identified from the survey data involved the peer mentors' ability to ask probing questions that made the first-year students to think more deeply about their field placement experiences (8 comments from 53 surveys). Another member of our MRU Education Department has previously observed that first-year students in our teacher education program often take a surface approach when they are journaling about their field placement experiences (Nickel, 2013). They simply describe the setting of a classroom rather than questioning and probing the learning and teaching transactions taking place within this environment.…”
Section: Probing Questions To Think Deepermentioning
confidence: 99%
“…A Professional Self-development Critical Reflection Scale (PSCRS) is indeed originally designed and validated to be a psychometrically sound tool which is purposefully used as a self-report questionnaire to measure the variable of students' professional self-development (see Appendix E). When drafting this research tool, the research team uses the ideas of Nickel (2013). Self-directed learning and self-education skills are measured with the Self-directed Learning Skills Scale (SLSS) that is constructed and validated by Ayyildiz and Tarhan (2015).…”
Section: Research Methods and Data Collection Instrumentsmentioning
confidence: 99%